HIF1A up‐regulates the ADORA2B receptor on alternatively activated macrophages and contributes to pulmonary fibrosis. Issue 11 (12th July 2017) - Philip, Kemly; Mills, Weng Tingting; Davies, Jonathan; Chen, Ning‐Yuan; Karmouty‐Quintana, Harry; Luo, Fayong; Molina, Jose G.; Amione‐Guerra, Javier; Sinha, Neeraj; Guha, Ashrith; Eltzschig, Holger K.; Blackburn, Michael R.
Abstract : Idiopathic pulmonary fibrosis (IPF) is a deadly chronic lung disease. Extracellular accumulation of adenosine and subsequent activation of the ADORA2B receptor play important roles in regulating inflammation and fibrosis in IPF. Additionally, alternatively activated macrophages (AAMs) expressing ADORA2B have been implicated in mediating adenosine's effects in IPF. Although hypoxic conditions are present in IPF, hypoxia's role as a direct modulator of macrophage phenotype and identification of factors that regulate ADORA2B expression on AAMs in IPF is not well understood. In this study, an experimental mouse model of pulmonary fibrosis and lung samples from patients with IPF were used to examine the effects and interactions of macrophage differentiation and hypoxia on fibrosis. We demonstrate that hypoxia‐inducible factor 1‐α (HIF1A) inhibition in late stages of bleomycin‐induced injury attenuates pulmonary fibrosis in association, with reductions in ADORA2B expression in AAMs. Additionally, ADORA2B deletion or pharmacological antagonism along with HIF1A inhibition disrupts AAM differentiation and subsequent IL‐6 production in cultured macrophages. These findings suggest that hypoxia, through HIF1A, contributes to the development and progression of pulmonary fibrosis through its regulation of ADORA2B expression on AAMs, cell differentiation, and production of profibrotic mediators. These studies support a potential role for HIF1A or ADORA2B antagonists in the treatment of IPF.—Philip, K., Mills, T. W., Davies, J., Chen, N.‐Y., Karmouty‐Quintana, H., Luo, F., Molina, J. G., Amione‐Guerra, J., Sinha, N., Guha, A., Eltzschig, H. K., Blackburn, M. R. HIF1A up‐regulates the ADORA2B receptor on alternatively activated macrophages and contributes to pulmonary fibrosis. FASEB J. 31, 4745–4758 (2017). www.fasebj.org